MANAJEMEN SUPERVISI PENDIDIK DALAM MENINGKATKAN HAFALAN PESERTA DIDIK DI KELAS 3 MI TAHFIDZ DARUL HIKMAH MENGANTI JEPARA TAHUN 2023 - Saifatillahil Wahidah; Ahmad Saefudin (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
Madrasah Ibtidaiyah Tahfidz Darul Hikmah Menganti Jepara, the children have been able to memorize several chapters of the Qur'an. This study aims to find out how to manage the learning process so as to produce graduates who are able to memorize several chapters of the Qur'an. The research method used is descriptive qualitative. Observation and interview are the tools used for data collection. The results of the research show that an educator in managing and supervising the learning process is directly on the implementation in schools in general. Because all planning such as time allocation, annual program, semester program all come from the school principal and from the Curriculum Deputy Head. The implementation process is that in the morning after entering class students perform Dhuha prayers in congregation in their respective classes, then continue with prayer and reading Asmaul Husna, greetings and greetings from the teacher, prayer before starting learning. After that, it continues with the previous/previous juz dzikroni and continues additional memorization which is guided by the teacher and followed by students. Then continue muroja'ah independently for 10 to 15 minutes after which the memorization is deposited to the teacher by bringing his achievement book as a sign that he has deposited his memorization. And for the evaluation carried out by means of written and oral tests. For follow-up, you can provide enthusiasm and motivation so that these students are more enthusiastic and Istiqomah in memorizing as well as during advanced classes.